An Economic Study on Value of Export and Import of All Minerals in India (International Journal of Food and Nutritional Sciences, 2022)
India is rich in minerals and however, the consumption of minerals and metal by Indians is low. Thisis general trend. This trend leads to low economic development. Hence a scientific economics study onthe Indian foreign trade in minerals including the export and import is necessary to promote this ventureand to frame a suitable mining policy. The study reveals that there has been a steady increase in the theIndia’s export value of all minerals. India can reclaim the first place in the India’s export value of allminerals trade, provided the Indian government pays more attention to the India’s export value of allminerals marketing activities, export promotional activities.